Evaluating Impact of Improved Land and Water Resources Practices on Water Runoff and Shallow Aquifer - International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2017)
In this study, 484 shallow wells were geo-referenced, mapped and studied in two districts, Bougouni and Koutiala, in southern Mali to understand the dynamics of groundwater recharge and relationship with rainfall in different seasons.